Study on Social, Religious and legal Positions Relating to child custody: Exploring Perspectives on Child Custody (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This study looks at the topic of child custody from a variety of different angles, including social,religious, and legal. Which In most cases, the decision on who will have custody of children in India ismade by a court with appropriate authority There are many different religions prevalent in India thus, eachreligion has its own canon of child custody rules that control the process by which a parent can seekcustody of their child. This is possible since India is a secular nation. The laws dealing with marriage andpersonal law always includes provisions for resolving concerns pertaining to child custody. In mostcases, the parent who can demonstrate financial stability, positive parenting qualities, and the capacityto cause the least amount of disruption to the child will be awarded physical possession by the court.